Voicelessness and exclusion: a systematic review of the (non)participation of low-income population in the design and governance of financial inclusion products and policies - Edward A. Osifodunrin; José Dias Lopes (Cogent Economics & Finance, 2025)
In this systematic literature review, we hope to (re)draw the attention of financial inclusion (FI) stakeholders to the voicelessness or non-participation of low-income populations (LIPs) in the design and governance of micro-financial services (MFSs) and other FI products and policies. Despite the global popularity of MFSs among LIPs, our goal is to spur deeper dialogue on making these services more responsive to the specific needs and welfare constraints of targeted LIP groups. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, we conducted 26 keyword-based queries on the Web of Science Core Collection, retrieving 3,957 studies and selecting 46 relevant to participatory FI. Findings reveal limited academic/industry focus on LIPs’ involvement in FI design and governance. Asia had the highest research concentration, followed by Africa and the Americas; Europe was absent. Using six criteria (inclusiveness, popular control, considered judgement, transparency, efficiency, and transferability), a study on rural Nepal emerged as the most comprehensive participatory model. Formal microcredit dominated research interest. High costs appear to be the main barrier to scaling participatory approaches. The review also surfaces concerns about elite capture and the quality of LIPs’ participation—issues crucial for guiding future research, product development, and policymaking.